PENERAPANMODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI KELAS VII SMPN 1 RIMBA MELINTANG TAHUN PELAJARAN 2015/2016 - Wulandari, Sri; ', Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to improve learning outcomes biology class VII SMP N 1 Rimba Melintang in the academic year 2015/2016 with the implementation of learning model Problem Based Learning (PBL). Conducted from January to May 2016. The subjects were students of class VII SMPN 1 Rimba Melintang in the academic year 2015/2016 with the number of 31 people consisting of 13 students and 18 female students. This research is a classroom action research (PTK) will be undertaken in two cycles with three meetings and go 1 time daily tests. The parameters in this study is the result of student learning that consists of the absorption of students and completeness of student learning, student activities and teacher's activities. The results showed that the learning outcomes of students has increased in the first cycle students' absorption of 77% (enough) and the second cycle 79% (enough). Mastery learning in the first cycle were completed and 64.52% increased in the second cycle is 77.42%. Activities of students in the first cycle of 76.97% (enough) and the second cycle increased to 83.06% (very good). Activities of teachers increased from 83.33% (good) and the second cycle 95.85% (very good). The learning model Problem Based Learning (PBL) can improve learning outcomes Biology class VII SMPN 1 Rimba Melintang in the academic year 2015/2016.Keywords: biology learning outcomes, learning Problem Based Learning (PBL)